Auxin Metabolism Is Involved in Fruit Set and Early Fruit Development in the Parthenocarpic Tomato “R35-P” - Zhang, Shaoli; Gu, Xin; Shao, Jingcheng; Hu, Zhifeng; Yang, Wencai; Wang, Liping; Su, Hongyan; Zhu, Luying (Frontiers in Plant Science, 2021)
Parthenocarpic tomato can set fruit and develop without pollination and exogenous hormone treatments under unfavorable environmental conditions, which is beneficial to tomato production from late fall to early spring in greenhouses. In this study, the endogenous hormones in the ovaries of the parthenocarpic tomato line ‘R35-P’ (stigma removed or self-pollination) and the nonparthenocarpic tomato line ‘R35-N’ (self-pollination) at four stages between preanthesis and postanthesis investigated using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). A nearly two-fold IAA (indoleacetic acid) content was found in ‘R35-P’ than in ‘R35-N’ at -2 and 0 days after anthesis (DAA). Except at -2 DAA, a lower ABA (abscisic acid) content was observed in Pe (stigma removed in ‘R35-P’) compared to that in Ps (self-pollination in ‘R35-P’) or CK (self-pollination in ‘R35-N’). After pollination, although the content of GA1 (gibberellins acid 1) in CK increased, the levels of GAs (gibberellins acids) were notably low. At all four stages, a lower SA (salicylic acid) content was found in Ps and CK than in Pe, while the content and change trend were similar in Ps and CK. The variation tendencies of JA (jasmonic acid) varied among Pe, Ps and CK at the studied periods. Further KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analyses of transcriptomic data identified 175 differentially expressed genes (DEGs) related to plant hormone signal transduction, including 63 auxin-related genes, 27 abscisic acid-related genes, 22 ethylene-related genes, 16 cytokinin-related genes, 16 salicylic acid-related genes, 14 brassinosteroid-related genes, 13 jasmonic acid-related genes and 4 gibberellin-related genes at -2 DAA and 0 DAA. Our results suggest that the fate of fruit set or degeneration occurred before anthesis in tomato. Auxins, whose levels were independent of pollination and fertilization, play prominent roles in controlling fruit set in ‘R35-P’, and other hormones are integrated in a synergistic or antagonistic way.